1991
DOI: 10.4037/15597768-1991-2010
|View full text |Cite
|
Sign up to set email alerts
|

Families: A Link or a Liability?

Abstract: Hospitalization in a critical care setting has multiple effects on patients and their families. For patients, it can be a frightening and dehumanizing experience, while families are confronted with stressors that can disrupt normal family functioning. The nurse is the pivotal figure in the health care system who can positively affect family coping through the support offered. With family needs met, they are then strengthened and able to support their family member. This article examines the roles and relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Apart from the use of presence by nurses, nursing research also explored the influence of social support from family members on critically ill patients. In general, the contribution of family support to patient recovery has been described as a part of the much broader social support system (Kupferschmid et al, 1991). Geary et al (1994) reported that ''someone with you'', e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the use of presence by nurses, nursing research also explored the influence of social support from family members on critically ill patients. In general, the contribution of family support to patient recovery has been described as a part of the much broader social support system (Kupferschmid et al, 1991). Geary et al (1994) reported that ''someone with you'', e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the research related to visiting in critical care units has focused on family needs with little emphasis on the perspective of the nurse at the bedside. In fact, very little is known about what strategies nurses actually use in working with visitors or the effectiveness of these strategies, although authors of critical care textbooks and a few articles have offered suggestions [see for example, Chulay, Guzzetta, and Dossey (1997), Hudak, Gallo, and Morton, (1998), Kupferschmid, Briones, Dawson, and Drongowski, (1991), Urden, Lough, and Stacy (1996)].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bucknall and Thomas (1996) argue that there is a sustained exposure to life threatening crises and higher levels of stress related to decision‐making. Although the role of the critical care nurse encompasses technical, physical and psychological aspects of caring; within the literature, the most cited studies on critical care concern three areas: communication (Dyer 1995, Caine 1991, Elliot & Wright 1999, Hupcey 1999, Jafar & Muayyad 2005); technology (Cooper 1993, Locsin 1995, Walters 1995) and the needs of family members (Molter 1979, Leske 1986, Kupferschmid et al. 1991, Johnson et al.…”
Section: Introductionmentioning
confidence: 99%